Evaluation of different types of Moroccan Phosphate Rock on phosphorus and other nutrient uptakes by oil palm (Elaeis guineensis Jacq.) seedlings - Khairuanuar, Norakmal (2021)
Malaysia has a total of 5.87 million ha of oil palm planted area and it is the world’s second largest palm oil producer. Malaysia has also subjected for 25.8% of world’s palm oil production and 34.3% of world’s oil palm exports. Phosphorus (P) is one of the most essential elements for plant growth but P deficiency is considered to be one of the major limitations for crop production on a global scale, in particular tropical acid soils. To fulfill the P demand for crop production, oil palm plantation in Malaysia has been relying heavily on the use of P fertilizer in particular phosphate rocks (PRs), due to its solubility in acid soils and lower cost. The reactivity of PRs used in Malaysia however are very low and will eventually affect the plant’s performance. Recently, PRs from different geographical locations are being transported into the Malaysian market. Moroccan Phosphate Rock (MPR) reserves a large production of phosphate in the market which can be a good alternative to the previous PR deposit. Hence, the aim of this study was to investigate the growth performance of different oil palm genotype seedling applied with different types of MPRs. An incubation study was conducted to evaluate the release of P in acid soils. 700g of two different acid soils (Munchong and Bungor series soils) were incubated with three different types of MPR (Type A, B and C) at the rate of 350 mg P kg-1 of soil for 15 weeks. Egyptian Phosphate Rocks (EPRs) was used as a comparison. Apart from that, a field study was also conducted on oil palm seedlings. Different rates and types of PRs was being evaluated for its effectiveness on N, P, K, Ca and Mg uptake. Five different rates of MPR Type B (0, 50, 100, 200 and 400mg P kg-1) were applied two times; first and fourth month of 8 months throughout the study into 20kg of mixture of topsoil (70%) and sand (30%) and put into polythene bag with the size of 20’x20’. While for the different types of MPR, the experiment was conducted simultaneously with the previous experiment. Three types of MPR were used (Type A, B and C) at the rate of 100 mg P kg-1 with EPR was chosen as a comparison. 4 months old of oil palm seedlings from two different genotypes (Felda Yangambi and Sime Darby Avros) were used. The treatments were carried out for 8 months and arranged in a Randomized Complete Block Design (RCBD) with 4replications. Meanwhile, a detection of organic acid from oil palm seedlings root exudates under P-stress condition was performed for the third study. As for the result, the changes of extractable P in soils treated with MPR is higher compared to the EPR. Munchong series soil showed a better soil property in term of nutrient absorption into the soils. The lower amount of Al oxides in Munchong soil series attributed to the higher changes of extractable P in soils. Meanwhile, the rates and types of PR application had a significant effect on the nutrient uptake of the oil palm seedlings. A positive correlation was obtained for all plant nutrients which indicate that application of PRs into the soil improves the nutrient in plant. The rate of PR application at 100 mg P kg-1 was found to be the optimum rate for P uptake of the oil palm seedlings. As for different types of PR application, MPR Type B was found to be superior in providing P for plant uptake. Lastly, the detection of organic acid exuded by the plant roots under P- stress condition resulted in the identification of two organic acids; oxalate and citrate. All in all, these findings bring to the conclusion that MPR Type B at the rate of 100mg P kg-1 has been identified as an optimum and affective amount in supplying sufficient P and others nutrient (N, K, Ca, and Mg) uptake to the oil palm seedlings. Hence, MPR Type B can be a good alternative to the current PR used in Malaysia.